2000
DOI: 10.1063/1.127055
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescent properties at nanometer resolution through Z-contrast scanning transmission electron microscopy

Abstract: We report the observation of porous structures in laser-ablation-deposited Y2O3:Eu thin films and their correlation with luminescent properties by a combination of transmission electron microscopy and Z-contrast scanning transmission electron microscopy (Z-STEM). Depending on growth conditions, a large density of voids is incorporated into the films, which leads to a much increased surface area. Cathodoluminescence imaging in the STEM directly reveals a 5 nm “dead layer” around each void, which is responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…More experiments are necessary to make a final conclusion or to propose a final model to describe the mechanism of the degradation process. Gao et al [21] observed porous structures in laserablation-deposited Y 2 O 3 :Eu thin films. Depending on growth conditions, a large density of voids was incorporated into the films, which leads to a much increased surface area.…”
Section: Resultsmentioning
confidence: 98%
“…More experiments are necessary to make a final conclusion or to propose a final model to describe the mechanism of the degradation process. Gao et al [21] observed porous structures in laserablation-deposited Y 2 O 3 :Eu thin films. Depending on growth conditions, a large density of voids was incorporated into the films, which leads to a much increased surface area.…”
Section: Resultsmentioning
confidence: 98%
“…A more recent example of STEM-CL is shown in Figure 4, showing a Eu-activated Y 2 O 3 phosphor material grown by laser ablation (Gao et al 2000). The structure is quite porous and a direct correlation was found between the size of the pores and luminescent efficiency.…”
Section: Studies Of Dislocationsmentioning
confidence: 96%